The economics of global green ammonia trade – "Shipping Australian wind and sunshine to Germany". (15th March 2023) - Egerer, Jonas; Grimm, Veronika; Niazmand, Kiana; Runge, Philipp
Highlights: Optimization model for the integrated assessment of the green ammonia value chain. Case study for ammonia trade between Australia and Germany in 2030. Sensitivity analysis on ammonia prices for technical and economic parameters. Cost comparison of conventional and green ammonia production. Abstract: This paper contributes to understanding the transformation of global energy trade to green energy carriers, focusing on green ammonia as the foreseeable first green hydrogen carrier. We provide a comprehensive overview of today's ammonia trade and assess scaling options for the trade of green ammonia. To that aim, we develop an optimization model for the integrated assessment of the green ammonia value chain that covers all steps from green ammonia production in an exporting country, up to delivery to a harbor in an importing country. The model endogenously chooses among different technology options and determines cost minimal operation. In a case study, we apply the model to the large-scale import of ammonia from Australia to Germany in a scenario for 2030. The results show that green ammonia can reach cost parity with gray ammonia even for moderate gas prices (but not necessarily with blue ammonia) if CO2 prices are high enough. We also provide a sensitivity analysis with respect to the interest rate and other key technical and economic parameters and show that cracking ammonia to provide pure hydrogen comes at a 45 % cost markup per MWh at the destination.